The expatriate entrepreneur: Drivers to migrate to South Africa - Sibahle K. Mathe; Ashika Maharaj (SA Journal of Human Resource Management)
Orientation: Expatriate entrepreneurs (EEs) willingly seek to relocate abroad independently and belong to the self-initiated expatriates (SIEs) group. They possess the classic behavioural characteristics of entrepreneurs, have the propensity to embrace risk and uncertainty and have high self-efficacy and control while seeking opportunities to initiate business development.